Land Fund and General Requirements for Land Use in the Republic of Uzbekistan: Theoretical and Practical Approaches (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
In this scientific article, the researcher examines how land use rights are being reshaped in the context of modern land reforms. The introduction of new forms of land ownership could not leave the relatively well-established institution of land use unchanged during the reform period.